In the Linguistic Paradise A Festschrift for E. Nolue Emenanjo - Ndimele, Ozo-mekuri; Emenanjọ, E. Nọlue (Nigerian festschrift series ;, 2019)
In the Linguistic Paradise is the second volume in the Nigerian Linguists Festschrift Series. The motivating force behind the establishment of the Festschrift Series is to honour outstanding scholars who have excelled in the study of languages and linguistics in Nigeria. This volume is dedicated to Professor E. Nolue Emenanjo, a celebrated linguist and a pioneer professor of Igbo Linguistics. The book is organised in five sections, as follows: Language, History and Society; Literature, Stylistics and Pragmatics; Applied Linguistics; Formal Linguistics; and Tributes. There are 15 papers in the first section the majority address the perennial problem of language choice in Nigeria. Section two contains 10 papers focusing on literature, stylistics and pragmatics. Section three contains 17 papers a sizeable number of which focus on language teaching and learning, two are on lexicography, while others are on language engineering. Section three contains 16 papers focusing on the core areas of linguistics. In section four a biographical profile of Professor E. Nolue Emenanjo and list of publications is presented, while Nwadike examines the contributions of Emenanjo in Igbo Studies.